An extensive study on the chemical diversity of lipophilic extractives from Eucalyptus globulus wood - Gominho, Jorge (2020)
Three mature Eucalyptus globulus trees with 40 years of age were studied at three height levels (0%, 35%, and 60% of total tree height) and at three radial regions (sapwood, inner and outer heartwood). The composition of lipophilic extracts was evaluated and an extensive list of 202 compounds was reported for the first time. The fatty acids were the major chemical family, representing 40.8% of the total compounds, followed by phytosterols (19.0%), aromatics (10.5%) and triterpenes (10.4%). Saturated fatty acids accounted for 74.2% of total compounds (C-16(:0), C-24(:0) and C-26(:0) were predominant), beta-Sitosteml and stigmastanol were the main sterols (80 and 7% respectively), while aromatics were mainly represented by syringic acid, 4-hydroxy-3,5-dimethoxybenzaldehyde, vanillic acid, and vanillin. The main triterpenes were asiatic and arjunolic acids.